2021
DOI: 10.3390/su13041965
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural Innovation and Sustainable Development: A Case Study of Rice–Wheat Cropping Systems in South Asia

Abstract: The rice–wheat cropping system is the main food bowl in Asia, feeding billions across the globe. However, the productivity and long-term sustainability of this system are threatened by stagnant crop yields and greenhouse gas emissions from flooded rice production. The negative environmental consequences of excessive nitrogen fertilizer use are further exacerbating the situation, along with the high labor and water requirements of transplanted rice. Residue burning in rice has also severe environmental concerns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 95 publications
0
9
0
Order By: Relevance
“…PA applies traditional farming practices with new technology, practices, and economic drivers to enhance sustainability in a dynamic balance [15]. Studies have reported positive outcomes from PA adoption, including economic savings in productivity factors [16], increasing yield and environmental sustainability [17], and improving food security and community economic vitality in developing regions [18]. The International Society for Precision Agriculture (ISPA) provides clarity and guidance on this important concept, to achieve the agricultural production quality, create production profits, and improve the efficiency of resource use and environmental sustainability [19].…”
Section: Introductionmentioning
confidence: 99%
“…PA applies traditional farming practices with new technology, practices, and economic drivers to enhance sustainability in a dynamic balance [15]. Studies have reported positive outcomes from PA adoption, including economic savings in productivity factors [16], increasing yield and environmental sustainability [17], and improving food security and community economic vitality in developing regions [18]. The International Society for Precision Agriculture (ISPA) provides clarity and guidance on this important concept, to achieve the agricultural production quality, create production profits, and improve the efficiency of resource use and environmental sustainability [19].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, organic amendment and mineral fertilizer recommendations should be fine tuned and extrapolated to spatial domains with relatively uniform agro-ecological characteristics, cropping practices, and socioeconomic conditions (Dobermann et al 2003). Key challenges in rice-based systems of Southeast Asia are thus to achieve regional food security and to increase farm incomes using site-specific integrated crop and nutrient management techniques (Tsujimoto et al 2019), and to avoid nutrient imbalances in view of achieving a sustainable development (Ullah et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…South Asian countries are considered the primary food bowl for rice ( Oryza sativa L.) and wheat ( Triticum aestivum L.), feeding one‐fifth of the global population (Nawaz et al., 2019; Saharawat et al., 2010). However, the intensive cultivation practices have threatened the system sustainability because of deteriorating soil health (Nawaz et al., 2017, 2021; Ullah et al., 2021) and weed infestation (Singh et al., 2012). Indeed, conventional practices of growing rice and wheat cause changes in soil structure, destroy soil physicochemical properties, decrease soil microbial activities (Mondal et al., 2016; Nadeem et al., 2020; Nawaz et al., 2021; Ullah et al., 2021), and deplete soil nutrient pool, resulting in poor soil quality (Nawaz et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, the intensive cultivation practices have threatened the system sustainability because of deteriorating soil health (Nawaz et al., 2017, 2021; Ullah et al., 2021) and weed infestation (Singh et al., 2012). Indeed, conventional practices of growing rice and wheat cause changes in soil structure, destroy soil physicochemical properties, decrease soil microbial activities (Mondal et al., 2016; Nadeem et al., 2020; Nawaz et al., 2021; Ullah et al., 2021), and deplete soil nutrient pool, resulting in poor soil quality (Nawaz et al., 2019). Conventional rice cultivation through flooding is also a major contributor to methane emission from the anaerobic decomposition of soil organic matter (SOM) (Liu & Wu, 2004).…”
Section: Introductionmentioning
confidence: 99%